Analysing the Problem of "Otherness" in The Painted Veil——Based on Beauvoir’s Existential Feminism Theory - Wang, Yunhan; Zhang, Xinchi; Zhang, Yixin (Transactions on Social Science, Education and Humanities Research, 2024)
William Somerset Maugham is a famous British novelist and playwright, known for his expertise in portraying characters and depicting the complexity of human nature. The novel The Painted Veil, one of Maugham’s representative works, focuses on the experience of the heroine Kitty and her changes of state of mind. It explores the process of female spiritual awakening from ignorance to independence, with distinct feminist features. At the time of the novel’s creation, the Western women’s liberation movement was in full swing. The wave of liberating women and the pursuit of equality swept the entire Western world, leaving footprints in Maugham’s literary works. This paper analyzes The Painted Veil through Beauvoir’s female theory and a feminist perspective, finding that it breaks the bondage and prejudice of the traditional female image at that time, creating a new image and value pursuit for women. It also reflects Maugham’s rejection of the portrayal of females as "the other," criticizes patriarchal society to some extent, and affirms feminist theory.